2011
DOI: 10.1186/1752-0509-5-149
|View full text |Cite
|
Sign up to set email alerts
|

In vivo kinetics of transcription initiation of the lar promoter in Escherichia coli. Evidence for a sequential mechanism with two rate-limiting steps

Abstract: BackgroundIn Escherichia coli the mean and cell-to-cell diversity in RNA numbers of different genes vary widely. This is likely due to different kinetics of transcription initiation, a complex process with multiple rate-limiting steps that affect RNA production.ResultsWe measured the in vivo kinetics of production of individual RNA molecules under the control of the lar promoter in E. coli. From the analysis of the distributions of intervals between transcription events in the regimes of weak and medium induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
86
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(92 citation statements)
references
References 32 publications
6
86
0
Order By: Relevance
“…Two studies reported in vivo measurements of the kinetics of P lac/ara-1 [21,22]. In these, the RNA is visible shortly after transcription occurs by tagging them with MS2d-GFP proteins [23].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported in vivo measurements of the kinetics of P lac/ara-1 [21,22]. In these, the RNA is visible shortly after transcription occurs by tagging them with MS2d-GFP proteins [23].…”
Section: Introductionmentioning
confidence: 99%
“…In our implementation, each time this reaction occurs, a value of τ S is drawn from a gamma distribution with mean of k M -1 and coefficient of variation (variance over the mean) of αMMathClass-bin-1MathClass-bin/2. With proper parameter values, the gamma distribution well approximates recent live cell measurements of intervals between productions of consecutive RNAs in E. coli [13,20]. We fitted the measurements of time intervals in [20] with the three-exponential model proposed in that work, and with a gamma distribution.…”
Section: Methodsmentioning
confidence: 99%
“…This approximation assumes that the elongation time is negligible, which relies on observation that the durations of the closed and the open complex formations (in the order of 10 3 s) [1,2,13,20] are much longer than elongation (in the order of 10 1 or 10 2 s) [21,22]. Moreover, in prokaryotes, translation is coupled to transcription [23], and can initiate as soon as the ribosome binding site region (RBS) of the RNA is formed (Shine-Dalgarno sequence) [24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations